Kajian Beban Emisi SO2, NO2 dan Partikulat dari Cerobong Boiler dengan Bahan Bakar Kayu pada PT X - Nabila Indah Wibisono; Novirina Hendrasarie (Jurnal Serambi Engineering, 2024)
The industrial revolution has led to an increase in the number of industries around the world, including Indonesia. PT X is one of the industries that produces emissions from wood-fired boiler stacks that have the potential to cause air pollution such as sulphur dioxide (SO2), nitrogen dioxide (NO2) and particulate matter. In this study, the emission load generated by PT X and the efficiency of the use of emission control devices were carried out. The high content of SO2, NO2 and particulates is 955.91 mg/Nm3, 1,744.92 mg/Nm3 and 1,354.21 mg/Nm3 produced from the boiler is above the quality standard. Therefore, emission control tools are needed to reduce the emission burden. The emission control tool used is cyclone dust collector. The cyclone dust collector acts as an air pollution control equipment and helps to remove large dust particles from the disposal of industrial processes. The efficiency of this mechanical dust collector increases with particle size. For larger particle sizes, this tool has a high efficiency. It is able to reduce SO2, NO2 and particulate emissions by 16%, 43% and 74% respectively. At this concentration it is already below the quality standard